Insight into the relationship between the cell culture model, cell trafficking and siRNA silencing efficiency - Capel, Victoria; Vllasaliu, Driton; Watts, Peter; Stolnik, Snow (Elsevier, 2016)
Despite research efforts, cell uptake processes determining siRNA silencing efficiency remain unclear. Here, we examine the relationship between in vitro cell culture models, cellular trafficking and siRNA silencing efficiency to provide a mechanistic insight on siRNA delivery system design. Model siRNA-polyplexes, based on chitosan as a ‘classical’ condensing agent, were applied to a panel of lung epithelial cell lines, H1299, A549 and Calu-3 and cell internalization levels, trafficking pathways and gene silencing assessed on exposure to pharmacological inhibitors. The data reveal striking differences in the internalization behaviour and gene silencing efficiency in the tested cell lines, despite their common lung epithelial origins. The model system’s silencing was lower where clathrin internalization pathway predominated in Calu-3, relative to silencing in H1299 cells where a non-clathrin internalization appears dominant. Increased silencing on endosomal disruption was apparent in Calu-3 cells, but absent when cellular internalization was not predominantly clathrin-mediated in A549 cells. This highlights that identifying cell trafficking pathways before incorporation of functional components to siRNA delivery systems (e.g. endosomolytic compounds) is crucial. The study hence stresses the importance of selection of appropriate cell culture model, relevant to in vivo target, to assess the gene silencing efficiency and decide which functionalities the ‘stratified siRNA silencing vector’ requires.